From Theory to Practice: EFL Student Teachers’ Teaching Experiences in “Kampus Mengajar” Program - Fauziah, Fauziah (English Education : English Journal for Teaching and Learning, 2025)
This study explores the EFL student teachers (STs) experiences during the “Kampus Mengajar” program, focusing on their transition from theoretical knowledge to practical classroom application. The “Kampus Mengajar” program, initiated by the Indonesian Ministry of Education, provides STs with the opportunity to teach in schools across diverse regions, thereby enhancing their pedagogical skills, adaptability, and professional identity. Using a qualitative approach, this research collected data through in-depth interviews, document analysis, and personal reflection. Findings show that STs’ participation in “Kampus Mengajar” enriched their competencies in lesson planning, classroom management, and instructional strategies based on student needs. Moreover, the program fostered confidence, reflective practice, and problem-solving skills, bridging the gap between university coursework and real-world teaching. Thus, this study provides important insights of experiential learning in teacher education and suggests that structured teaching placements like “Kampus Mengajar” are essential for preparing competent and reflective EFL educators.